"Tem que saber mexer": uma etnografia sobre trabalhadores manuais, moradores da periferia de Santa Maria - RS - Oliveira, Cristiane Savian de (2014)
The purpose of this dissertation is to analyse the representations and social practices of manual workers that live in the periphery of Santa Maria, RS. For this, we seek to understand how these men constitute themselves as subjects in this context, through their narratives and work practices, the interpersonal relationships that are formed and the knowledge acquired in the workplace. From the participant observation and ethnographic writing, we sought to reflect how this particular type of worker wich apparently lives in a situation of disadvantage in brazilian society, perpetuates his knowledge.